Small bowel polyp resection using device‐assisted enteroscopy in Peutz‐Jeghers Syndrome: Results of a specialised tertiary care centre. Issue 2 (1st March 2020) - Perrod, G; Samaha, E; Perez‐Cuadrado‐Robles, E; Berger, A; Benosman, H; Khater, S; Vienne, A; Cuenod, C‐A; Zaanan, A; Laurent‐Puig, P; Rahmi, G; Cellier, C
Abstract : Introduction: Enteroscopy resection of small bowel polyps in Peutz‐Jeghers syndrome has only been described in small case series. Herein, we aimed to assess the efficacy of enteroscopy resection of small bowel polyps within a specialised tertiary care centre and the impact on intraoperative enteroscopy. Methods: This was an observational single‐centre study. All adult Peutz‐Jeghers syndrome patients followed in the Predisposition Digestive Ile‐de‐France network who underwent an endoscopic resection of at least one small bowel polyp ≥ 1 cm by enteroscopy between 2002–2015 were included. Small bowel polyps were detected under a dedicated screening programme by previous capsule endoscopy and/or magnetic resonance enterography, performed every 2–3 years. Complete treatment was defined as the absence of polyps ≥ 1 cm after conventional endoscopic resection. Intraoperative enteroscopy or surgical resection were indicated in incomplete treatments. The overall complete treatment rate including conventional enteroscopy and intraoperative enteroscopy was also considered. Results: Endoscopic resection of 216 small bowel polyps (median: 8.6 per patient, size: 6–60 mm) was performed by 50 enteroscopies in 25 patients (mean age: 36 years, range: 18–71, 56% male) with small bowel polyp ≥ 1 cm. Twenty‐three patients (92%) underwent 42 screening capsule endoscopies and 14 (57%) had 23 magnetic resonance enterographies during a median follow‐up of 60 months. Complete treatment was achieved in 76%. Intraoperative enteroscopy and surgical resection were performed in four (16%) and two (8%) patients. Intraoperative enteroscopy improved by 16% the complete treatment rate and the overall rate was 92%. The complication rate was 6%. Conclusion: This long‐term study confirmed the efficacy and safety of endoscopic resection of small bowel polyps in Peutz‐Jeghers syndrome. Intraoperative enteroscopy can be a complementary approach in selected cases.